Nilai-Nilai Pendidikan Multikulturalisme dalam Film Ngeri-Ngeri Sedap Karya Bene Dion Rajagukguk - Ponco Adi Nugroho; Sukarni Suryaningsih; Ken Widyatwati; M. Suryadi; Rezki Amelia Anggraeni (Universitas Pancasakti Tegal, 2025)
This study aims to analyze the values of multicultural education in the film Ngeri-Ngeri Sedap directed by Bene Dion Rajagukguk. The film portrays the social and cultural dynamics within a Batak family, highlighting diversity and intergenerational conflicts related to the acceptance of culture and identity. Ngeri-Ngeri Sedap was selected for its explicit exploration of diversity within the family context, depicting how family members with different backgrounds navigate differences in worldview, culture, and identity. The multiculturalism approach is employed to understand how the film addresses issues of diversity and serves as a medium for fostering social awareness in society. This research utilizes Stuart Hall’s theory of representation to analyze how the values of multicultural education are depicted in Ngeri-Ngeri Sedap. The analysis refers to the five multicultural values proposed by Wakano: (1) inclusivity, representing acceptance of differences; (2) prioritization of dialogue as a means of achieving mutual understanding; (3) humanism, which emphasizes the dignity of each individual; (4) appreciation of diversity; and (5) patriotism, stressing the importance of unity in diversity. The findings of this study are expected to contribute to the fields of literature and cultural studies, and to enhance understanding of the role of media in promoting multicultural education values in Indonesia, particularly within the context of family and pluralistic society.